(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2022)
This paper addresses the challenges to the effectiveness of the right to the city, based on the concepts of Henri Lefevbre, articulated with the concepts of communicative action, participatory democracy and public and private autonomy in Habermas. It initially identifies the main factors that generate the current crisis of the cities, analyzes legal and theoretical aspects related to the right to the city, and seeks to reflect on the essential elements for an active popular participation, communicative processes, and democratic management of the cities. As a result, it was observed that the need for an effective democratic procedure, based on legitimate communicative processes, capable of assuring the various social actors, through rational and argumentative discursive activity, the expression of their will, so that they can contribute, in cooperation, to the formation of political decisions.